2020
DOI: 10.1074/jbc.ra119.009978
|View full text |Cite
|
Sign up to set email alerts
|

An atypical lipoteichoic acid from Clostridium perfringens elicits a broadly cross-reactive and protective immune response

Abstract: Clostridium perfringens is a leading cause of food-poisoning and causes avian necrotic enteritis, posing a significant problem to both the poultry industry and human health. No effective vaccine against C. perfringens is currently available. Using an antiserum screen of mutants generated from a C. perfringens transposon-mutant library, here we identified an immunoreactive antigen that was lost in a putative glycosyltransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…TLR stimulation may be limited to either TLR2 or TLR4 and not TLR21. It is possible, in chickens, that highly virulent C. perfringens strains are least immunogenic in terms of innate sensing ( 52 ). In vivo experiments have also demonstrated that C. perfringens -induced TLR signaling in chickens is not sufficient to elicit cytokine expression such as IFN-γ due in part to an increase in IL-4 and IL-10 cytokine expression ( 14 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…TLR stimulation may be limited to either TLR2 or TLR4 and not TLR21. It is possible, in chickens, that highly virulent C. perfringens strains are least immunogenic in terms of innate sensing ( 52 ). In vivo experiments have also demonstrated that C. perfringens -induced TLR signaling in chickens is not sufficient to elicit cytokine expression such as IFN-γ due in part to an increase in IL-4 and IL-10 cytokine expression ( 14 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…For opsonophagocytosis assays, C. jejuni cells were incubated with fresh heparinized chicken blood and either naïve chicken serum or pooled chicken serum (from responder and non-responder birds) according to the method previously described by Goyette-Desjardins et al (2016) with modifications ( Wenzel et al, 2020 ). To prepare the bacterial cells, C. jejuni 81-176 was grown on BHI plates.…”
Section: Methodsmentioning
confidence: 99%
“…Little has been explored about the consequences of structural modifications in LAM before being released. Reports suggest that a glycosylation system or addition/breaking off of molecules is critical to delivering amphipathic molecules, like LTA from Clostridium perfringens or LTA from Staphylococcus aureus (Kho and Meredith, 2018;Wenzel et al, 2020). Mtb is capable of substituting α-(1→2)-Manp-linked residues with α-(1→4)-linked methylthio-D-xylose (MTX) residues, and modifying the branches of arabinofuranosides and mannose-capped versions, decreasing recognition of antibodies that are currently used in diagnostic methods based on immunoassays (Taghikhani and Moukhah, 2016;Angala et al, 2017;Choudhary et al, 2018).…”
Section: Advances In the Use Of Serum Lam Assay To Tb Diagnosismentioning
confidence: 99%